Analisis Bauran Pemasaran Dalam Meningkatkan Kepuasan Pengunjung Kolam Renang Kendedes di Desa Sragi - Cindy Rohadatul ‘Aisy Jannah; Hanik Amaria; Nik Haryanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research method uses qualitative research, researchers use Purposive Sampling sampling. Data Collection Techniques using interviews, documentation, observation. Data Validity Testing Techniques using source triangulation and data analysis techniques using several stages (Sugiyono, 2020): organizing data, grouping based on categories, themes, and answer patterns, testing assumptions or problems that exist against data, looking for alternative explanations for data and writing research results. The formulation of the problem in this study is how is the marketing strategy in increasing visitor satisfaction of the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency and what factors support and hinder the implementation of marketing strategies in increasing visitor satisfaction of the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency. The purpose of this study is how is the marketing strategy in increasing visitor satisfaction of the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency and what factors support and hinder the implementation of marketing strategies in increasing visitor satisfaction of the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency. The results of this study are that the Kendedes swimming pool uses a 4 P marketing mix (Product, Price, Place & Promotion). Consumer satisfaction is the conformity of expectations that customers and visitors to the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency feel that the facilities and infrastructure and services from the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency are in accordance with the expectations of customers and visitors to the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency. Then the factor of interest in reuse, that customers and visitors to the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency feel satisfied so they want to come back to the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency. The next factor is the willingness to recommend, that customers and visitors to the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency provide information and share experiences with others so that other people are also interested in visiting the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency. The supporting factors for the promotion of the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency are social media because it is free of charge and of course used by many people. The inhibiting factors for the promotion of the Kendedes swimming pool in Sragi Village, Talun District, Blitar Regency are limited to using only social media and not doing other more effective forms of promotion.Send feedback,Side panels,History,Saved